Transformasi Pembelajaran PAI Berbasis Hukum Islam melalui Penguatan Literasi Bahasa Indonesia di Era Society 5.0 - Al Bazzar; Hajrah B.; Maslawani Maslawani (Lembaga Yasin AlSys, 2026)
The transformation of Islamic Religious Education (PAI) learning has become a focus in various studies, but research that specifically discusses the integration of Islamic law-based PAI learning through the strengthening of Indonesian language literacy in the Society 5.0 era remains limited. This study aims to describe the transformation of Islamic law-based PAI learning through the strengthening of Indonesian language literacy. This study employed a qualitative approach with a descriptive design, involving 2 PAI teachers and 30 secondary school students selected through the purposive sampling technique. Data were collected through observation, in-depth interviews, and documentation and were then analyzed using thematic analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results show that strengthening Indonesian language literacy in PAI learning can increase student engagement, contextual understanding of Islamic law concepts, as well as critical thinking and communication skills. In addition, learning becomes more interactive, reflective, and relevant to the needs of the 21st century. These findings contribute to the development of the concept of literacy-based PAI learning as a transformational approach in Islamic education. The conclusion of the study emphasizes that the integration of literacy in PAI learning is important for improving the quality of students’ religious understanding and higher-order thinking skills. The practical implication is that teachers and educational institutions need to develop innovative and literacy-based learning strategies so that PAI learning becomes more contextual, communicative, and adaptive to the demands of the Society 5.0 era.